IMPLEMENTASI PEMBINAAN DAN PENGAWASAN TERHADAP BAZNAS PROVINSI SUMATERA SELATANTENTANG PENGELOLAAN ZAKAT - Ihsan, Nurul; Hadi, Sutrisno (Muamalah, 2019)
The government has accommodated the management of Zakat by establishing a zakat institution, BAZNAS. The huge potential of Zakat funds makes the Zakat institution should receive more attention such as guidance and supervision from the government such as other government institutions, the form of BAZNAS Institution which is considered Non-Structural which is responsible to the President without being under any ministry, good to be studied more deeply actually guidance or supervision of the institution. In South Sumatra the place where the author conducted the Study There is an Amil Zakat Institution in South Sumatra Province which recently was conducted by the Financial Audit of the institution. From here the author wants to know how to guide and supervise the Amil Zakat BAZNAS institutions, especially the South Sumatra Province BAZNAS. The approach used in this study is a normative approach, while the normative approach to seeing and understanding the Guidance and Supervision of the Government of the South Sumatra Province BAZNAS in the management of zakat is related to Law No. 23 of 2011, is qualitative in nature, meaning that data analysis is directed towards data that is based on quality, quality and characteristics that are in fact valid and occur in BAZNAS, South Sumatra Province. The results of the research analysis Coaching carried out on BAZNAS is in the form of facilitation, socialization and education. Which in the application of guidance carried out by the Government in this case is the Ministry of Religion, Governor, Mayor, and Regent in accordance with its hierarchy. Whereas the supervision carried out / imposed by the Law on the community is access to information about the management of Zakat carried out by BAZNAS and LAZ wherever they are, as well as an audit of the annual report on the performance of BAZNAS in the form of Sharia Financial Audit and Audit. Also the delivery of information in the event of irregularities in the management of zakat made by BAZNAS. The issuance of Government Regulation (PP) No. 14 of 2014 concerning the implementing rules of Law Number 23 Year 2011 concerning the management of Zakat is a support, as a legal umbrella or regulating how the responsibility of BAZNAS in each work program is carried out.